Effect of roasting pretreatment on fatty acids, oxidative stability, tocopherols, and antioxidant activity of gurum seeds oil. (July 2021) - Karrar, Emad; Mohamed Ahmed, Isam A.; Manzoor, Muhammad Faisal; AL-Farga, Ammar; Wei, Wei; Albakry, Zainab; Sarpong, Frederick; Wang, Xingguo
Abstract: The impact of roasting on the quality attributes and storability of gurum seeds oil is underestimated. Thus, it was investigated the influence of conventional oven roasting (COR) treatments (at 140, 160, and 180 °C) on the quality attributes and storage stability of gurum seeds oil. The acid value (AV), peroxide value (PV), fatty acids (FAs), vitamin E, total polyphenol, oxidative stability (OS), and antioxidant activity of gurum seeds oil prepared from roasted and unroasted seeds were evaluated. COR treatments significantly increased the oil yield (27–37%), PV (0.75–0.84 mequiv of O2/kg of oil), OS (4.02–8.56 h), total tocopherols (560.70–805.25 mg/100 g), and polyphenols (22.39–29.24 mg GAE/kg of oil). While COR treatments DPPH IC50% value significantly decreased from (23.88–14.87 mg/mL). COR produce a slight change in the FAs' contents of oils and also improved the storage stability during 15 days of accelerated storage at 60 °C. Generally, gurum seeds oil contains substantial amounts of nutrients which could be improved by COR treatments. Obtained results suggested that the COR of gurum seeds is a more suitable pre-processing method. These results can significantly contribute to furthermore study of seed oils and their characteristics. Highlights: Roasting temperatures affects the chemical compositions, oxidative stability, antioxidant activity of oils. The yields of oils increased significantly as roasting temperature also increased. Peroxide value increased progressively initially and afterward decreased in higher roasting temperatures. Roasting the gurum seeds afforded an increase in the amounts of the tocopherols, polyphenol and antioxidant activity. Roasting for different times had a favorable impact on the oxidative stability after 15 days of storage at 60 °C.